The Question of assigning the posts of Magistri Militum during the reign of emperor Zeno (474–491) - Leszka, Mirosław (Balcanica Posnaniensia. Acta et studia, 2021)
Originating from Isauria, Emperor Zeno was a ruler who struggled more against internal opponents who made attempts to deprive him of power (usurpations of Basiliskos 475-476, Martian 479, Illus and Leontius 484-488) than against external enemies. Zeno's career, before becoming a ruler, was of a military nature. He was certainly a comes domesticorum and magister militum per Orientem, and some scholars believe that he may also have held the position of magister militum per Thracias and magister militum praesentalis. The aim of the article is to make an attempt to answer the question what the emperor, who had rich military experience, was guided by when appointing magistri militum. A review of the available information concerning the appointment of magistri militum by Zeno leads to the conclusion that these posts were a means of recruiting or rewarding people whose support the emperor needed for some reason. The highest positions of command were relatively often given to members of the imperial family or the families of influential personalities at the imperial court or their protégés.